Nucleotide pool-sensitive selection of the transcriptional start site in vivo at the Salmonella typhimurium pyrC and pyrD promoters. - Sørensen, K I (1993)
Expression of the Salmonella typhimurium pyrC and pyrD genes is regulated in response to fluctuations in the intracellular CTP/GTP pool ratio. The repressive mechanism involves the formation of a stable secondary structure (hairpin) at the 5' ends of the transcripts that precludes translational initiation by sequestering sequences required for ribosomal binding. The potential for hairpin formation is controlled through CTP/GTP-modulated selection of the transcriptional start site. Substitution of nucleotides in the region of transcriptional initiation has revealed that selection of the transcriptional start point in vivo depends on the nucleotide context within the initiation region and the nucleoside triphosphate pool ratios. For maximal control in response to CTP/GTP pool ratios, the wild-type CCGG start site motif appears to be optimal. Changing the -35 region in the pyrC promoter to the consensus sequence, or replacement of the pyrC promoter with the lac promoter from Escherichia coli, has served to illustrate that the ability of the RNA polymerase to select the initiation site in response to the intracellular nucleoside triphosphate pools is not promoter specific but is determined by the kinetic properties of the initiating RNA polymerase during the formation of the first phosphodiester bond of the transcript.